Novel metal-dielectric metameric optical filters for optical security devices - 郭榕 陈楠 陈鹭剑 王晓忠 蔡志平 李延凯 卜轶坤 (Optoelectronics letters, 2014)
Optical security devices play an essential role in the fight against counterfeiting. In this paper, we study and design a pair of metal-dielectric optical filters based on metameric effect, which offer a hidden image effect by the color shift at a specific angle of observation. Compared with all-dielectric multilayer system, the metal-dielectric multilayer structure has larger color shift with varying incident angle, higher color saturation and fewer layers. Finally, the stacks with 5 layers and 7 layers are achieved, and the color difference index is only 0.71, which shows good metameric matching effect. Simultaneously, the sensitivity of filters to deposition errors is analyzed when the thickness deviation is ±2%, and the results show that the two filters have good manufacturability.